2019
DOI: 10.1038/s41598-019-49898-0
|View full text |Cite
|
Sign up to set email alerts
|

Infectious phage particles packaging antibiotic resistance genes found in meat products and chicken feces

Abstract: Bacteriophages can package part of their host’s genetic material, including antibiotic resistance genes (ARGs), contributing to a rapid dissemination of resistances among bacteria. Phage particles containing ARGs were evaluated in meat, pork, beef and chicken minced meat, and ham and mortadella, purchased in local retailer. Ten ARGs (blaTEM, blaCTX-M-1, blaCTX-M-9, blaOXA-48, blaVIM, qnrA, qnrS, mecA, armA and sul1) were analyzed by qPCR in the phage DNA fraction. The genes were quantified, before and after pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 59 publications
2
60
0
Order By: Relevance
“…As in previous studies [ 23 , 24 ], filtered and concentrated phage suspensions were treated with chloroform (1:10 ( v / v )) to rule out the possible presence of vesicles containing DNA, vigorously vortexed for 5 min and centrifuged at 16,000× g for 5 min. The aqueous phase was incubated with DNase I (100 units/mL) to eliminate any free DNA in the samples outside the phage particles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in previous studies [ 23 , 24 ], filtered and concentrated phage suspensions were treated with chloroform (1:10 ( v / v )) to rule out the possible presence of vesicles containing DNA, vigorously vortexed for 5 min and centrifuged at 16,000× g for 5 min. The aqueous phase was incubated with DNase I (100 units/mL) to eliminate any free DNA in the samples outside the phage particles.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm that only the ARGs from the phage particles were evaluated, several controls were performed as previously described [ 24 ]. Briefly, an aliquot of each sample after DNase treatment and before desencapsidation was included in the qPCR in parallel with the DNA sample to confirm the absence of each ARG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in isolates belonging to CC PAS 1 in our study the most commonly identified mobile element carrying oxa23 was a bacteriophage phiOXA. Reports of the carriage of antibiotic resistance genes in prophages have become more common in recent years (75)(76)(77), but it is thought that this is generally a rare occurrence (78).…”
Section: Discussionmentioning
confidence: 99%
“… 91 There is controversial evidence of phage transduction of resistance in vivo and, additionally, multiple lines of evidence indicating that phages from multiple environments are circulating ARGs. 91 93 Compelling and recent in vivo studies involving head-to-head competition of two E. coli strains in a mouse gut demonstrated that phage-mediated genetic exchange is responsible for adaptation of an invading E. coli species, underlining the likelihood of phage transduction as a mechanism of AMR spread. 94 The proportion of mobilized AMR due to phage transduction in human enteric disease remains an open question.…”
Section: Part II Questionable Arms Deals: the Evolution And Acquisitmentioning
confidence: 99%